Violenza di genere, media e diritti delle donne - Giovanna Truda (Culture e Studi del Sociale)
The work intends to reflect on the role of the media in communicating gender violence and how they contribute to the construction of public opinion and the collective imagination. An analysis that, between women's rights and the socio-cultural dynamics of violence contexts, analyzes the stereotypes and prejudices that permeate the communication of the phenomenon.